THE EFFECT OF ONLINE CUSTOMER RATING, CASH ON DELIVERY PAYMENT SYSTEM, AND ONLINE CUSTOMER REVIEWS ON PURCHASING DECISIONS: - Suci Mulyana; Nurainun; Khairina AR (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This thesis aims to find out the influence of Online Customer Rating, Cash on Delivery Payment System, and Customer Reviews on Purchasing Decisions. The research method used in preparing this thesis uses quantitative methods, with the sampling method using non-probability sampling techniques and purposive sampling techniques. The sample in this study amounted to 120 samples. The data was collected through a survey distributing questionnaires via hard copy to consumers who made purchases and also used the Bukalapak marketplace. This study uses multiple linear regression analysis methods. The results of this study found that online customer ratings (X1) partially have a negative and significant effect on purchasing decisions (Y), cash on delivery payment systems (X2) partially have a positive and significant effect on purchasing decisions (Y), and online customer reviews (X3) partially have a negative and significant effect on purchasing decisions (Y). The results of this study indicate that purchasing decisions on the Bukalapak website are strongly influenced by the Cash on Delivery Payment System variable (X2). Meanwhile, for simultaneous testing, it was found that the variables Online Customer Rating (X1), Cash on Delivery Payment System (X2), and Online Customer Reviews (X3) together have an effect on purchasing decisions on the Bukalapak website.